Dynamic contribution analysis of badminton-smash-motion with consideration of racket shaft deformation (a model consisted of racket-side upper limb and a racket) - Koike, S.; Hashiguchi, T. (Procedia Engineering, 2014)
The purpose of this study was to develop a methodology that quantifies the contributions of the racket-side upper limb joint torques and shaft restoring torque to the generation of racket head speed during the badminton smash motion. The racket-side upper limb was modelled as successive rigid segments, such as upper arm, forearm and hand segments. The racket shaft was divided into a set of rigid segments connecting to its adjacent segments via virtual joints with rotational spring. The contributions of the joint torque term, motion-dependent term, gravitational term, and shaft restoring torque term to the generation of racket head speed were calculated from the equation of motion for the system consisting of racket-side upper limb and racket. A new algorithm which converts motion dependent term into other terms was proposed to investigate the main factor of the motion dependent term. The results showed that 1) the motion dependent term was the largest contributor to the generation of head speed prior to the impact, and 2) the shaft restoring torque term was positive contributor to the generation of motion dependent term over the forward swing period in the badminton smash motion.